Partial flocculation for spray drying of spherical mixed metal oxide particles. Issue 10 (16th May 2018) - Ehrhart, Brian D.; Ward, Barbara J.; Richardson, Benjamin M.; Anseth, Kristi S.; Weimer, Alan W.
Abstract: Particles are an important design consideration for many proposed solar thermochemical water splitting reactor concepts. These particles must maintain physical integrity and chemical performance at very high temperatures (>900°C) while flowing within a system. Spray drying is a commonly used, scalable method to produce solid spherical particles that have the best opportunity to meet these requirements. Spray drying is used to produce hercynite (FeAl2 O4 ) particles using pH‐modification of a charge‐stabilized sol. This process involves inducing partial flocculation in nanoparticle suspensions to yield larger particles that are spherical and structurally robust. A commercial boehmite suspension is characterized along with a mixture of the boehmite suspension with an iron oxide suspension. Zeta potential near zero and peak yield stress measurements at the same pH indicate flocculation, but associated sedimentation behavior is not observed. The behavior of both the boehmite‐only and mixed suspensions both seem to be driven by the behavior of the boehmite suspension alone. Spray dried particles from the mixed suspension at the critical pH gave significantly larger and more spherical particles, which also indicates flocculation. This relatively simple technique shows promise for new mixed‐metal material formulations and scalable applications.